PENGARUH PENDIDIKAN KESEHATAN TENTANG PENANGANAN BALITA TERSEDAK (CHOKING) TERHADAP PENGETAHUAN IBU DI PAUD AISYIYAH KECAMATAN COMAL KABUPATEN PEMALANG - Azizah, Salma Nurul; Nugroho, Santoso Tri; Indriono, Anik (PENA NURSING, 2024)
Background: Choking is an emergency situation that can occur to everyone, especially babies and children. This condition can make a person experience blockage in the respiratory tract and necessary to be given immediate first aid to prevent hypoxia and death. Mothers who are caring for babies and children need to understand how to provide first aid when the babies or children they are caring for are choking. Objective: aims to help improve mothers' knowledge and skills in providing first aid when their babies and children experience choking. Method: This study uses a pre-experiment approach with one group pretest posttest design. The sample used in this study was 30 respondents. Results: The average score of mothers' knowledge about choking management before health education was carried out was 57.2. Meanwhile, the average score of mothers' knowledge about choking management after providing health education increased to 88.93. The Wilcoxon test results obtained p value = 0.001. Conclusion: There is an influence of health education regarding handling toddler’s choking on increasing mothers' knowledge and skills in handling those matter.